BUDGET IN THE MIDST OF CRISIS: REFOCUSING AND PUBLIC PARTICIPATION IN CENTRAL LAMPUNG'S FINANCIAL POLICY (2020-2022) - Imam Fatkuroji; Yulianto; Maulana Mukhlis (RADJA PUBLIKA, 2025)
This study examines the implementation of budget refocusing in Central Lampung Regency during the COVID-19 crisis (2020), focusing on integrating participatory budgeting principles. The research aims to (1) describe the budget refocusing process while upholding participatory principles (active citizen participation, increased citizen authority, social justice, transparency), (2) identify the implications of budget refocusing on regional financial policies (responsiveness, efficiency, accountability, stakeholder uncertainty, government-community relations), and (3) analyze the challenges faced in implementing budget refocusing regarding community involvement, government support, resource limitations, distrust, technology use, and public attitudes. Using a qualitative descriptive approach, the study explores the dynamics of budgeting in the region. Results indicate that participatory budgeting and budget refocusing are significant in meeting urgent needs, allowing community involvement in planning, and ensuring access to participation for all groups, especially marginalized ones. Strengthening communication between the government and the community is essential for budget refocusing to reflect the needs of the community.